2013
DOI: 10.1016/j.polymdegradstab.2013.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic copolymers containing 3-indolylfulgides/indolylfulgimides: Synthesis and photochemical properties in toluene and as films

Abstract: Photochromic indolylfulgimides covalently attached to polymers have beneficial properties for optical switching. A 3-indolylfulgide and two 3-indolylfulgimides with one or two polymerizable styrene groups attached on the nitrogen atom(s) were synthesized. Copolymerization with methyl methacrylate (MMA) provided linear copolymers (one styrene group) or a cross-linked copolymer (two styrene groups). The properties of the monomers and copolymers in toluene or as thin films were characterized. The new copolymers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…18 Indolylfulgides and indolylfulgimides are regarded as promising candidates to be used in optical data storage devices because they usually display great thermal stability in solvents and polymer films. 18,27,28,34 A previous study found that the fluorinated indolylfulgides had outstanding resistance to thermal stress in the closed form, however, the open form was less stable and degraded rapidly at 80°C.…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…18 Indolylfulgides and indolylfulgimides are regarded as promising candidates to be used in optical data storage devices because they usually display great thermal stability in solvents and polymer films. 18,27,28,34 A previous study found that the fluorinated indolylfulgides had outstanding resistance to thermal stress in the closed form, however, the open form was less stable and degraded rapidly at 80°C.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…46 Indolylfulgides and indolylfulgimides can endure hundreds to thousands of photochemical cycles (back and forth conversion between the two key forms) before degrading by 20%. 2,[27][28][29]41 A mechanism of photochemical degradation for a methyl indolylfulgide was proposed by Yokoyama (Scheme 20). 28 The major degradation pathway involves a 1,5-hydrogen migration from a methyl group to the carbonyl oxygen on the anhydride ring.…”
Section: Photochemical Stabilitymentioning
confidence: 99%
See 3 more Smart Citations